Penegakan Hukum terhadap Tindak Pidana Penipuan terhadap Konsumen dalam Usaha Jual Beli Online di Kota Kupang - Intan Andreaningrum Kadja; Thelma S.M Kadja; Orpa G. Manuain (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
Legal protection against fraud against consumers in online business has been regulated in the Criminal Code Articles 378 and 379 and Article 28 paragraph (1) jo. Article 45 paragraph (2) of the ITE Law regulates false news that results in consumer losses in Electronic Transactions. This research is a research that uses an empirical approach method, namely an approach based on the type of data and data analysis. The results of this study found (1) Law enforcement against criminal acts of fraud against consumers in the online buying and selling business in Kupang City runs based on existing legal rules, namely both the Criminal Code and the ITE Law, namely Article 378 of the Criminal Code and Article 28 paragraph (1) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. (2) Efforts to protect consumers in criminal acts of fraud on e-commerce sites in Kupang City are preventive efforts to prevent the occurrence of such criminal acts. Then repressive efforts to provide criminal sanctions in accordance with applicable regulations. This effort can be done by the way victims can report criminal acts of fraud by visiting law enforcement agencies for further processing.